Highly dispersed zirconium oxide-aluminum oxide ceramic powder and preparation method thereof

By uniformly dispersing yttrium oxide on the surface of alumina particles, the problem of zirconia agglomeration is solved, the sintering activity and mechanical properties of zirconia-alumina ceramic powder are improved, and the hardness and toughness of the ceramic splitter are improved. And simplifies the preparation process.

CN119118637APending Publication Date: 2024-12-13WUHAN UNIV OF TECH +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411278165.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Zirconia in existing zirconia and alumina composite ceramics is prone to agglomeration, affecting the performance of the ceramics, especially when zirconia content is increased to improve fracture toughness.

Method used

By uniformly dispersing yttrium oxide on the surface of alumina particles, a stable zirconia particles are formed by alkali leaching method, and a stable zirconia/yttrium precursor package is formed with an acetylacetonate zirconium/yttrium precursor package in water with acetylacetonium/yttrium precursor. Cover the structure, reduce agglomeration, and control the particle size and crystallinity of zirconia during drying and calcining.

Benefits of technology

The high dispersion of zirconia on the surface of alumina is achieved, the sintering activity and mechanical properties of composite ceramics are enhanced, the hardness and toughness of the ceramic chopper are improved, and the preparation process is simplified, the cost is reduced, and it is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118637A_ABST
    Figure CN119118637A_ABST
Patent Text Reader

Abstract

The invention relates to highly dispersed zirconia-alumina ceramic powder and a preparation method thereof, the ceramic powder takes alumina particles as a skeleton, and yttria-stabilized zirconia particles are uniformly dispersed and attached to the surfaces of the alumina particles. According to the highly dispersed zirconium oxide-aluminum oxide ceramic powder provided by the invention, tetragonal-phase zirconium oxide is uniformly dispersed on the surface of aluminum oxide, agglomeration of zirconium oxide and aluminum oxide powder is effectively avoided due to tight combination of a precursor and hydroxyl, and the highly dispersed zirconium oxide-aluminum oxide ceramic powder has good sintering activity and mechanical properties and is beneficial to improvement of hardness and toughness of a ceramic chopper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum oxide, and in particular relates to a highly dispersed zirconium oxide-aluminum oxide ceramic powder and a preparation method thereof. Background Art

[0002] A splitter is a wire bonding tool with a capillary-like precision microstructure, which can connect the electrodes and lead terminals of IC chips to each other through wires. Ceramic splitters have important applications in the field of semiconductor and microelectronic packaging due to their excellent properties such as high hardness, high toughness, high wear resistance and long service life. ZrO2 toughened Al2O3 composite ceramics (ZTA ceramics) have excellent low-temperature aging resistance, thermal stability and fracture toughness, and are an excellent material for preparing ceramic splitters.

[0003] In ZTA ceramics, toughening is often achieved by introducing a second phase. Among them, Al2O3 composite ceramics toughened by Y2O3-stabilized ZrO2 have outstanding low-temperature anti-aging properties, thermal stability, fracture toughness and other excellent properties, and have therefore been widely studied. In CN113620329A, yttria-stabilized zirconia-coated alumina powder is prepared by rotary chemical vapor deposition. The ceramics obtained by further firing the alumina-zirconia nanocomposite powder have the performance advantages of high hardness and high density. However, when the content of zirconium oxide is further increased to improve the fracture toughness, since Al2O3 and ZrO2 are two phases, chemical bonds or physical adsorption cannot be formed at the microscopic level, and the agglomeration of ZrO2 is particularly prominent, which affects the performance of subsequent ceramic products. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a highly dispersed zirconia-alumina ceramic powder and a preparation method thereof in view of the deficiencies in the prior art. The ceramic powder has a high zirconia content and the zirconia is evenly dispersed on the surface of the alumina particles, thus solving the problem of easy agglomeration of zirconia.

[0005] The invention provides a highly dispersed zirconium oxide-aluminum oxide ceramic powder. The ceramic powder uses aluminum oxide particles as a skeleton, and yttria-stabilized zirconium oxide particles are uniformly dispersed and attached to the surface of the aluminum oxide particles.

[0006] According to the above scheme, the aluminum oxide particles are α-Al2O3, and D50 is 100-700nm.

[0007] According to the above scheme, the particle size of the yttria-stabilized zirconia particles is 8 to 39 nm, and yttria accounts for 3 to 9% of the molar amount of zirconia.

[0008] The present invention also provides a method for preparing the highly dispersed zirconium oxide-aluminum oxide ceramic powder, the specific steps of which are as follows:

[0009] 1) dissolving NaOH in water to obtain a NaOH solution, and adding alumina powder while stirring after the temperature of the NaOH solution returns to room temperature, until the alumina powder is evenly dispersed in the NaOH solution to obtain a dispersion A;

[0010] 2) the dispersion A obtained in step 1) is fully stirred, then allowed to stand, the supernatant is removed, and the remaining portion is centrifuged, washed with deionized water, dried and ground to obtain aluminum oxyhydroxide;

[0011] 3) dispersing the hydroxy aluminum oxide obtained in step 2) in deionized water to obtain a hydroxy aluminum oxide dispersion, then adding zirconium acetylacetonate and yttrium acetylacetonate hydrate while stirring to obtain dispersion B, then placing the obtained dispersion B in an ultrasonic resonance mixer for thorough oscillation and mixing to obtain a slurry, then vacuum drying and calcining the obtained slurry to obtain a semi-finished powder, and then washing, drying and grinding the obtained semi-finished powder to obtain a highly dispersed zirconium oxide-alumina ceramic powder.

[0012] According to the above scheme, the concentration of the NaOH solution in step 1) is 5-20wt%.

[0013] According to the above scheme, the alumina powder in step 1) is α-Al2O3, and D50 is 100-700nm.

[0014] According to the above scheme, the mass ratio of the alumina powder to the NaOH solution in step 1) is 1:5-20.

[0015] According to the above scheme, the concentration of the aluminum oxyhydroxide dispersion in step 3) is 40 to 80 wt%.

[0016] According to the above scheme, in step 3), the mass ratio of the total mass of zirconium acetylacetonate and yttrium acetylacetonate hydrate to aluminum hydroxide is 0.5-5:1, and yttrium oxide accounts for 3-9% of the molar amount of zirconium oxide.

[0017] According to the above scheme, the acceleration of the acoustic resonance mixer in step 3) is 40-90 m / s 2 The oscillation mixing time is 5 to 20 minutes.

[0018] According to the above scheme, the calcination process conditions in step 3) are: heating to 600-1000°C at a heating rate of 5-8°C / min at room temperature, and keeping the temperature for 2-7 hours. In this process, zirconium acetylacetonate and yttrium acetylacetonate hydrate are calcined into oxides to generate yttria-stabilized zirconium oxide particles. The particle size and crystallinity of the generated zirconium oxide can be controlled by adjusting the calcination conditions.

[0019] The present invention also includes ceramics prepared from the highly dispersed zirconium oxide-aluminum oxide ceramic powder. For example, the highly dispersed zirconium oxide-aluminum oxide ceramic powder is prepared into ceramic splitters and other products by spark plasma sintering technology.

[0020] The present invention forms hydroxyl groups on the surface of Al2O3 by an alkali leaching method, selects acetylacetone-type zirconium / yttrium precursors, utilizes its steric hindrance effect in water, uniformly disperses and grafts with hydroxyl groups on the surface of Al2O3, forms a stable structure of zirconium / yttrium precursor-coated Al2O3 powder, reduces agglomeration during drying and calcining, makes Y2O3-stabilized ZrO2 highly dispersed and attached around Al2O3 particles with uniform particle size, and can enhance the sintering activity of zirconium oxide-aluminum oxide composite ceramic powder.

[0021] The beneficial effects of the present invention are: 1. In the highly dispersed zirconia-alumina ceramic powder provided by the present invention, tetragonal zirconia is uniformly dispersed on the surface of alumina. Since the precursor is closely combined with the hydroxyl group, the agglomeration of zirconia and alumina powders is effectively avoided, and the powder has good sintering activity and mechanical properties, which helps to improve the hardness and toughness of the ceramic splitter. 2. The preparation method of the present invention has simple steps, relatively low cost, safe and controllable process, and is easy to prepare industrially. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD comparison diagrams of samples prepared in Example 2 (marked at 600° C.), Example 6 (marked at 800° C.) and Example 8 (marked at 1000° C.) of the present invention;

[0023] Figure 2 TEM images of the products prepared in Example 2 and Examples 5-8 at different calcination temperatures;

[0024] Figure 3 Transmission electron microscope image and element distribution map of the sample prepared in Example 2;

[0025] Figure 4 (a), (b), and (c) are respectively surface SEM images of the polished ZTA ceramics obtained after sintering the zirconium oxide-aluminum oxide ceramic powders obtained in Example 1, Example 3, and Example 2 under different oscillating mixing accelerations;

[0026] Figure 5 (a), (b), and (c) are comparison diagrams of the toughness, hardness, and density of the ceramics obtained by sintering the samples obtained in Example 2 and Examples 5-8 at 1350°C, 1400°C, 1450°C, 1500°C, and 1550°C, respectively;

[0027] Figure 6It is the infrared spectra of aluminum oxide, aluminum acetylacetonate, the product of the slurry obtained in step S4 of Example 2 after vacuum drying, and zirconium acetylacetonate. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below using embodiments in conjunction with the accompanying drawings.

[0029] The present invention is described in detail below with reference to the accompanying drawings.

[0030] Example 1

[0031] A highly dispersed zirconium oxide-aluminum oxide ceramic powder, the preparation method of which comprises the following steps:

[0032] S1. Take 10g of sodium hydroxide (purity ≥99.9wt%) and 100g of deionized water and put them into a polytetrafluoroethylene tank. Stir for 5min until the sodium hydroxide is completely dissolved. After the solution temperature drops to room temperature (27°C), add 10g of α-Al2O3 powder (purity ≥99.9wt%) with a D50 of 250nm while stirring. Stir for 5min until the α-Al2O3 powder is evenly dispersed in the solution to obtain dispersion A.

[0033] S2, the dispersion A was magnetically stirred at a speed of 800 r / min for 60 min, then allowed to stand for 24 hours, the supernatant was removed, and the remaining part was centrifuged at a speed of 8000 r / min for 5 min, the supernatant was poured out and then deionized water was added for washing, the centrifugation and washing steps were repeated until the pH value of the supernatant was neutral, and then placed in a vacuum drying oven at 80° C. for 12 h, and taken out and ground to obtain aluminum hydroxide;

[0034] S3, take 8g of aluminum hydroxide and add it to 10g of deionized water, disperse it evenly at a stirring speed of 500r / min, then add 7.98g of zirconium acetylacetonate and 0.442g of yttrium acetylacetonate hydrate while stirring to obtain dispersion B;

[0035] S4. Place dispersion B in an acoustic resonance mixer and set the acceleration to 50 m / s. 2 , the oscillation mixing time is 15 minutes, and the slurry is obtained after ultrasonic resonance mixing;

[0036] S5, vacuum drying the slurry at 70°C for 10 hours, placing the dried product in a crucible, heating it to 600°C at a constant heating rate of 5°C / min at room temperature, and calcining it for 3 hours to obtain a semi-finished product powder;

[0037] S6. Wash the semi-finished powder with deionized water, dry it, and finally grind it fully to obtain highly dispersed zirconium oxide-aluminum oxide ceramic powder.

[0038] Example 2

[0039] A highly dispersed zirconium oxide-aluminum oxide ceramic powder, the preparation method of which is similar to that of Example 1, except that: in step S4, the dispersion B is placed in an acoustic resonance mixer, and the acceleration is set to 70 m / s 2 , the shaking mixing time is 15 minutes.

[0040] Example 3

[0041] A highly dispersed zirconium oxide-aluminum oxide ceramic powder, the preparation method of which is similar to that of Example 1, except that: in step S4, the dispersion B is placed in an acoustic resonance mixer, and the acceleration is set to 90 m / s 2 , the shaking mixing time is 15 minutes.

[0042] Example 4

[0043] A highly dispersed zirconium oxide-aluminum oxide ceramic powder, the preparation method of which is similar to that of Example 2, except that: the mass of sodium hydroxide in step S1 is 20 g.

[0044] Example 5

[0045] A highly dispersed zirconium oxide-aluminum oxide ceramic powder, the preparation method of which is similar to that of Example 2, except that: the calcination temperature in step S5 is 700°C.

[0046] Example 6

[0047] A highly dispersed zirconium oxide-aluminum oxide ceramic powder, the preparation method of which is similar to that of Example 2, except that: the calcination temperature in step S5 is 800°C.

[0048] Example 7

[0049] A highly dispersed zirconium oxide-aluminum oxide ceramic powder, the preparation method of which is similar to that of Example 2, except that: the calcination temperature in step S5 is 900°C.

[0050] Example 8

[0051] A highly dispersed zirconium oxide-aluminum oxide ceramic powder, the preparation method of which is similar to that of Example 2, except that: the calcination temperature in step S5 is 1000°C.

[0052] like Figure 1Shown are XRD comparison diagrams of samples prepared in Example 2 (marked at 600°C), Example 6 (marked at 800°C) and Example 8 (marked at 1000°C). In the figure, 3Y-ZrO2+Al2O3 is a mixed powder obtained by ball milling of yttria-stabilized zirconia powder (purchased from Aladdin) and alumina powder (α-Al2O3 with a D50 of 250nm). Ball milling process: add 5% ethanol by mass of the powder for wet milling, the mass ratio of the ball milling medium to the powder is 7:1, the ball milling speed is 350rpm, and the ball milling time is 1 hour. By comparison, it can be seen that with the increase of calcination temperature, the crystallinity of zirconium oxide in the sample will also increase. Compared with 3Y-ZrO2, the sample prepared in the present application has a higher proportion of tetragonal zirconium oxide crystal (t-ZrO2), which is more conducive to the toughening of ceramics, while 3Y-ZrO2 contains monoclinic zirconium oxide (m-ZrO2), which has no toughening effect on ceramics.

[0053] Figure 2 The transmission electron microscope images of the products prepared at different calcination temperatures of Examples 2 and 5-8 are shown in FIG. 1 , wherein the gray represents alumina particles, and the black particles are yttria-stabilized zirconia. It can be clearly seen in the transmission electron microscope image that small yttria-stabilized zirconia particles are attached to the large alumina surface. The lower right image is a statistical comparison of the average particle size of zirconia in the products obtained at different calcination temperatures. The results show that the size of zirconia particles gradually increases with the increase of calcination temperature. Considering that the phase change during the sintering process of ceramic powder will promote the sintering of the powder, and the small-sized particles will promote the heat and mass transfer of the mixed powder during the sintering process, and promote the densification of ceramic sintering, the optimal calcination temperature is 600°C.

[0054] Figure 3 The transmission electron microscope image and element distribution diagram of the sample prepared in Example 2 show that in the zirconium oxide-alumina ceramic powder, where aluminum is aggregated, zirconium is also aggregated, indicating that zirconium oxide is evenly distributed and highly dispersed in the alumina matrix.

[0055] The zirconium oxide-aluminum oxide ceramic powders obtained in Example 1, Example 2, and Example 3 under different oscillating mixing accelerations were respectively loaded into graphite molds for pre-compression, and the pre-compression pressure was 0.09 tons. Subsequently, the graphite molds loaded with the ceramic powders were placed in an SPS sintering system for sintering. The sintering system was: starting from room temperature under vacuum, the temperature was raised to 1400° C. at a rate of 100° C. / min, and the pressure was gradually increased to 0.4 tons. The temperature and pressure were maintained for 10 minutes to obtain ZTA ceramics. Figure 4 (a), (b), and (c) are respectively the surface SEM images of the polished ZTA ceramics obtained by sintering the zirconium oxide-aluminum oxide ceramic powders obtained in Example 1, Example 3, and Example 2 under different oscillating mixed accelerations. The white one is zirconium oxide and the black one is aluminum oxide. By comparison, it can be seen that Example 2 has a high performance under the conditions of 70 m / s 2At this time, zirconium oxide and aluminum oxide can be fully mixed and highly dispersed. Too much or too little acceleration will make the zirconium oxide distribution uneven.

[0056] The samples obtained in Example 2 and Examples 5-8 were respectively placed in graphite molds for pre-compression, and the pre-compression pressure was 0.09 tons. Subsequently, the graphite molds filled with ceramic powder were placed in an SPS sintering system for sintering: the temperature was raised from room temperature to the sintering temperature (1350°C, 1400°C, 1450°C, 1500°C, 1550°C) at a rate of 100°C / min under vacuum, and the pressure was gradually increased to 0.4 tons. The temperature and pressure were maintained for 10 minutes to obtain ZTA ceramics. Figure 5 (a), (b), (c) are respectively the toughness, hardness and density comparison diagrams of the ceramics obtained by sintering the samples obtained in Example 2 and Examples 5-8 at 1350°C, 1400°C, 1450°C, 1500°C and 1550°C. It can be seen that the powder of Example 2 calcined at 600°C can achieve the best mechanical properties when prepared at a sintering temperature of 1400°C, indicating that it has a high sintering activity. Taking the sample of Example 2 as an example, the properties of the ceramics calcined at different temperatures are shown in Table 1 below:

[0057] Table 1

[0058]

[0059] Figure 6 The infrared spectra are of alumina (Al2O3, purchased from Aladdin), aluminum acetylacetonate (Al(acac)3, purchased from Aladdin), the product of the slurry obtained in step S4 of Example 2 after vacuum drying (denoted as hydroxyl Al2O3+Zr(acac)4), and zirconium acetylacetonate (Zr(acac)4, purchased from Aladdin). By comparison, it can be seen that compared with ordinary alumina and zirconium acetylacetonate, the hydroxyl peak of the product of the slurry obtained in step S4 of Example 2 after vacuum drying is wider, indicating that the hydroxyl content of alumina is higher after modification with S1 and S2 hydroxyl groups, and after the acoustic resonance of S4 zirconium acetylacetonate and zirconium acetylacetonate and yttrium acetylacetonate hydrate, the methyl peak of zirconium acetylacetonate disappears, indicating that the hydroxyl groups on the surface of hydroxy alumina react with the methyl groups of zirconium acetylacetonate to form hydrogen bonds, indicating that the zirconium acetylacetonate reaction in Example 2 is grafted on the surface of alumina, thereby avoiding the problem of zirconium oxide self-agglomeration when a large amount of zirconium oxide is doped. At the same time, by comparing the product of the slurry obtained in step S4 of Example 2 after vacuum drying and the infrared spectrum of aluminum acetylacetonate, it can be seen that aluminum acetylacetonate is generated on the surface of alumina, indicating that zirconium acetylacetonate successfully reacts with the coordinated unsaturated metal aluminum ions on the surface of the alumina support to generate aluminum acetylacetonate and zirconium ions, and the zirconium ions replace the original aluminum ions as the coordinated ions on the surface. The whole process is a chemical reaction mixing, and zirconium and aluminum are tightly combined, which effectively avoids self-agglomeration of zirconium oxide and is also conducive to the uniform distribution of zirconium oxide on the surface of alumina.

Claims

1. A highly dispersed zirconium oxide-aluminum oxide ceramic powder, characterized in that: The ceramic powder uses aluminum oxide particles as a skeleton, and yttria-stabilized zirconium oxide particles are uniformly dispersed and attached to the surface of the aluminum oxide particles.

2. The highly dispersed zirconium oxide-aluminum oxide ceramic powder according to claim 1, characterized in that: The aluminum oxide particles are α-Al2O3, and D50 is 100-700nm.

3. The highly dispersed zirconium oxide-aluminum oxide ceramic powder according to claim 1, characterized in that: The particle size of the yttria-stabilized zirconium oxide particles is 8-39 nm, and the yttria accounts for 3-9% of the molar weight of the zirconium oxide.

4. A method for preparing the highly dispersed zirconium oxide-aluminum oxide ceramic powder according to any one of claims 1 to 3, characterized in that: The specific steps are as follows: 1) dissolving NaOH in water to obtain a NaOH solution, and adding alumina powder while stirring after the temperature of the NaOH solution returns to room temperature, until the alumina powder is evenly dispersed in the NaOH solution to obtain a dispersion A; 2) the dispersion A obtained in step 1) is fully stirred, then allowed to stand, the supernatant is removed, and the remaining portion is centrifuged, washed with deionized water, dried and ground to obtain aluminum oxyhydroxide; 3) dispersing the hydroxy aluminum oxide obtained in step 2) in deionized water to obtain a hydroxy aluminum oxide dispersion, then adding zirconium acetylacetonate and yttrium acetylacetonate hydrate while stirring to obtain dispersion B, then placing the obtained dispersion B in an ultrasonic resonance mixer for thorough oscillation and mixing to obtain a slurry, then vacuum drying and calcining the obtained slurry to obtain a semi-finished powder, and then washing, drying and grinding the obtained semi-finished powder to obtain a highly dispersed zirconium oxide-alumina ceramic powder.

5. The method for preparing highly dispersed zirconium oxide-aluminum oxide ceramic powder according to claim 4, characterized in that: The concentration of the NaOH solution in step 1) is 5-20wt%; the alumina powder in step 1) is α-Al2O3, and D50 is 100-700nm; the mass ratio of the alumina powder in step 1) to the NaOH solution is 1:5-20.

6. The method for preparing highly dispersed zirconium oxide-aluminum oxide ceramic powder according to claim 4, characterized in that: Step 3) The concentration of the aluminum oxyhydroxide dispersion is 40 to 80 wt%.

7. The method for preparing highly dispersed zirconium oxide-aluminum oxide ceramic powder according to claim 4, characterized in that: Step 3) The mass ratio of the total mass of the zirconium acetylacetonate and the yttrium acetylacetonate hydrate to the aluminum oxide hydroxide is 0.5-5:1, and the yttrium oxide accounts for 3-9% of the molar amount of the zirconium oxide.

8. The method for preparing highly dispersed zirconia-alumina ceramic powder according to claim 4, characterized in that: Step 3) The acceleration of the acoustic resonance mixer is 40 to 90 m / s 2 The oscillation mixing time is 5 to 20 minutes.

9. The method for preparing highly dispersed zirconium oxide-aluminum oxide ceramic powder according to claim 4, characterized in that: Step 3) calcination process conditions are: heating to 600-1000° C. at a heating rate of 5-8° C. / min at room temperature, and keeping the temperature for 2-7 hours.

10. A ceramic prepared from the highly dispersed zirconia-alumina ceramic powder according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • High-voltage and single-crystal ternary positive electrode material and preparation method thereof

    CN107293744A

  • Preparation method of alumina-zirconia nano composite powder

    CN113620329A

  • Preparation method of nano-zirconia toughened nano-alumina ceramic

    CN117383914A

  • Method of obtaining and alumina ceramic material

    RU2738880C1